A CROSS-SECTIONAL STUDY ON THE KNOWLEDEGE AND AWARENESS OF COLORECTAL CANCER AMONG THE GENERAL POPULATION OF DISTRICT KARAK AND KOHAT KHYBER PAKHTUNKHWA (Journal of Medical & Health Sciences Review, 2025)
Background: Colorectal cancer (CRC) is one of the most common malignant tumors in the world. This study aimed to assess the level of CRC knowledge and awareness among university students and local residents in the districts of Kohat and Karak, Khyber Pakhtunkhwa (KPK), Pakistan.Methods: A descriptive cross-sectional study was conducted from August 20, 2024, to July 20, 2025, targeting university students at Kohat University of Science and Technology, as well as local residents from the district of KPK, Pakistan. The data was collected through a structured questionnaire, which was designed to assess their knowledge, attitudes, and practices related to CRC.Results: The overall sample comprised 800 participants with a mean knowledge score of 6.1 2.3 points on the 10-point assessment scale, serving as the baseline reference for all comparative analyses. Female participants demonstrated significantly more positive attitudes toward screening (77.8% vs 63.6%) and higher compliance with preventive practices. Participants from medical and health sciences backgrounds achieved significantly higher knowledge scores (7.4 1.9) compared to those from other academic disciplines, highlighting the critical role of specialized education in health literacy development. The findings highlight the urgent need for targeted educational interventions, healthcare system improvements, and policy initiatives to address CRC awareness and prevention in this region. The study contributes valuable baseline data for CRC prevention efforts in Pakistan and demonstrates the importance of comprehensive, multi-dimensional assessment in understanding health awareness and behavior.